Application of the Spatial Durbin Model (SDM) to Analyze the Factors Affecting Poverty in Maluku Province in 2024 - Najla Attamimi; Ronald John Djami; Novita Serly Laamena (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2026)
Poverty is defined as a condition in which individuals are unable to meet the minimum basic needs necessary for a dignified life. In Indonesia, particularly in Maluku, poverty remains a critical problem, exacerbated by the low quality of human resources and limited access to education, health care, and employment opportunities. This study aims to analyze the factors that significantly influence poverty in Maluku Province in 2024 and to build a poverty model using the Spatial Durbin Model (SDM). This research applies a statistical method known as the Spatial Durbin Model (SDM), which is a development of the Spatial Autoregressive Model (SAR). Thus, this model not only includes spatial lag on dependent variables, but also includes spatial lag on independent variables. Based on the calculations, it was found that the factors that significantly influence poverty are the average length of schooling and the labor force participation rate . An value of 96.46% and an AIC of 54.831 indicate that the model SDM provides good results in explaining the poverty variations in Maluku Province.